Uplink power control scheme for spectral efficiency maximization in NOMA systems - Bilal Ur Rehman; Mohammad Inayatullah Babar; Gamil Abdel Azim; Muhammad Amir; Hesham Alhumyani; Mohammed S. Alzaidi; Majid Alshammari; Rashid Saeed (Alexandria Engineering Journal, 2023)
Non-orthogonal multiple access (NOMA) has recently gained much research attention as a possible multiple access solution for fifth-generation (5G) wireless communication. The NOMA can further enhance spectral performance compared with orthogonal multiple access (OMA). This paper focuses on the joint optimization problem of power control and user grouping by considering the uplink NOMA system. The power control issues are solved using a linear programming approach and three alternative algorithms solve user grouping: Randomly, 2-Opt, and the Hybrid. The numerical results show that the proposed solution for power control and user-grouping achieves significant spectral performance compared to OMA and existing schemes reported in the literature with lower system complexity for uplink NOMA systems.